Rewritable glycochips. - Harris, L; Schofield, W; Doores, K; Davis, B; Badyal, J (2009)
We describe microarraying of carbohydrates for protein screening using either disulfide bridge or Schiff base imine immobilization chemistries on plasmachemical deposited functional nanolayers. The commonly observed issue of nonspecific background binding of proteins is overcome by spotting carbohydrates through a protein-resistant overlayer yielding spatially localized interaction with a reactive functional underlayer.